Tecmesa en Sófocles: esposa real de Ayante / Tecmessa in Sophocles: the real wife of Ajax - Carmen Morenilla Talens (Asparkía, 2014)
RESUMEN: Tecmesa, la cautiva de Ayante en la obra homónima de Sófocles, ha sido estudiada desde la perspectiva de su relación con el héroe; ha sido vista como la esclava sumisa que soporta el mal carácter de Ayante, lo que es considerado una muestra de la sumisión de la mujer al varón en la Atenas clásica. Un análisis más detenido de la tragedia muestra que Sófocles creó un personaje más complejo, cuya posición social es equivalente a la de la esposa. En esta caracterización desempeña un papel esencial la maternidad de Tecmesa. ABSTRACT: Tecmessa, the captive of Ajax in Sophocles’ play, has been studied from the standpoint of her relationship with the hero. She has been viewed as the submissive captive that bears the bad-tempered Ajax. Tecmessa character is considered a sign of the women submission to men in Ancient Athens. An in-depth analysis of Sophocles’ play will show that Sophocles configured a more intricate character whose social position is equivalent to wife's one. On this characterization, the maternity of Tecmessa plays an important role.